1961
DOI: 10.1017/s0021859600049765
|View full text |Cite
|
Sign up to set email alerts
|

The osmotic pressure and the concentration of some solutes of the intestinal contents and the faeces of the cow, in relation to the absorption of the minerals

Abstract: In the cows' intestine there is no isotony with the blood serum. In the upper part of the small intestine the chyme is strongly hypertonic but as it passes along the intestinal tract to the large intestine it becomes more and more hypotonic. The hypertony in the small intestine is not due to inorganic elements but is caused by organic non-electrolytes.In the large intestine hypotony is the result of strong selective absorption of sodium against a concentration gradient.This is an important aspect of the sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

1963
1963
1994
1994

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 28 publications
4
13
0
Order By: Relevance
“…A decrease in sodium concentration in digesta water occurs between the caecum and the rectum in many mammals (van Weerden 1961;Alexander 1962Alexander , 1965Edmonds 1967). Potassium concentration appears to be more variable.…”
Section: (F) Rates Of Absorption Of Water and Electrolytesmentioning
confidence: 99%
“…A decrease in sodium concentration in digesta water occurs between the caecum and the rectum in many mammals (van Weerden 1961;Alexander 1962Alexander , 1965Edmonds 1967). Potassium concentration appears to be more variable.…”
Section: (F) Rates Of Absorption Of Water and Electrolytesmentioning
confidence: 99%
“…Several authors have suggested that low sodium intake could possibly contribute to the development of hypomagnesaemic tetany (Frens 1955;Paterson and Crichton 1960;Ross 1961;Lehr 1962;Butler et al 1963;Kemp 1964), while others have discussed its effect on animal physiology ( van Weerden 1961;Bott, Denton, Goding, and Sabine 1964). Smith and Aines (1959) induced severe sodium deficiency in dairy cows by prolonged feeding of rations containing about 0.02% Na, and suggested a requirement of 21 g per day Na for lactating dairy cows.…”
Section: Calciummentioning
confidence: 99%
“…In (van Weerden, 1961) and humans (Kalser, Williams, Peterson & Smitherman, 1964) isotonicity is approached with distal movement of digesta within the small intestine. However, it is still a matter of contention whether water is actively absorbed from the small intestine (e.g.…”
Section: Cation and Water Inter-relations In Ileal Effluentmentioning
confidence: 99%